Artificial Intelligence dan Filsafat Ilmu: Bagaimana Filsafat Memandang Kecerdasan Buatan Sebagai Ilmu Pengetahuan - Arditya Prayogi; Riki Nasrullah (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
Artificial intelligence is a concept of implanting knowledge in machines to be able to carry out activities or activities like humans do, which by implanting artificial intelligence, has the aim of helping humans in completing everything that humans cannot do. This understanding then raises the question of whether artificial intelligence then becomes part of science itself. This article is compiled with a qualitative approach based on literature studies assisted by content analysis methods. From the results of the study, it is obtained that artificial intelligence is included in the understanding of the intermediary domain which in principle runs and becomes part of science, both theoretical and empirical. This makes artificial intelligence not only have philosophical implications for epistemological status, but also axiologically and ontologically which are part of the philosophy of science. Not only that, artificial intelligence also requires practical consequences with which artificial intelligence becomes part of science itself